A Dynamic Analysis of Pricing and Investment in Circular Economy with Learning-By-doing - Zhang, Ru (Issues in Economics and Business, 2024)
In this paper, we explore the optimal control problem of a monopolist’s pricing and recycling investment strategies under learning-by-doing within a circular economy. The model incorporates both virgin and recycled resources in production, and accounts for the accumulation of knowledge through recycling activities. We show that: (i) the monopolist’s recycling investment and pricing strategies evolve over time as a result of learning-by-doing, leading to operational efficiency gains; (ii) the monopolist’s private incentives for recycling are lower than the social optimum, resulting in an underinvestment problem; (iii) the gap between private and social incentives highlights the need for regulatory interventions to promote sustainable recycling practices. Our analysis identifies the existence of a steady-state equilibrium and examines how knowledge accumulation dynamically influences the firm’s cost structure and pricing strategies. The findings offer valuable insights into the long-term interactions between pricing, recycling investments, and sustainability objectives in a monopolistic market, with broader implications for the promotion of a circular economy.